Developing a hybrid, carbon/glass fiber-reinforced, epoxy composite automotive drive shaft - Abu Talib, Abdul Rahim; Ali, Aidy; Badie, Mohamed A.; Che Lah, Nur Azida; Golestaneh, Amirreza Fahim (Elsevier, 2010)
In this study, a finite element analysis was used to design composite drive shafts incorporating carbon and glass fibers within an epoxy matrix. A configuration of one layer of carbon–epoxy and three layers of glass–epoxy with 0°, 45° and 90° was used. The developed layers of structure consists of four layers stacked as [+45glass°/-45glass°/0carbon°/90glass°]. The results show that, in changing carbon fibers winding angle from 0° to 90°, the loss in the natural frequency of the shaft is 44.5%, while, shifting from the best to the worst stacking sequence, the drive shaft causes a loss of 46.07% in its buckling strength, which represents the major concern over shear strength in drive shaft design.